Efektivitas Media Video dalam Pembelajaran - Permata Fayzah; Amelia Ikhwayuna; Rasilvi Allinsia; Nur Azmi Alwi; Yarisda Ningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
In the learning process, students often encounter various obstacles. One common challenge is their difficulty in understanding the material presented by teachers, especially when the explanations are too abstract. To address this issue, appropriate instructional media are needed to help achieve learning objectives. The use of such media can support teachers in delivering content more effectively. As science and technology continue to evolve, instructional media must also adapt to create a learning environment that aligns with current developments. One form of media that can be utilized is educational video. This study aims to explore the use of video media in delivering instructional content. The method used is a literature review of previous research findings. The results indicate that video-based learning media can serve as an effective tool for teachers to present learning materials in a more engaging and comprehensible way.